KECURANGAN, SISTEM PERPAJAKAN, KEADILAN PAJAK, DAN DISKRIMINASI TERHADAP PERSEPSI ETIKA ATAS PENGGELAPAN PERPAJAKAN - Firmansyah, Firmansyah; Riyanto, Agus; Krismonika, Krismonika; Gantur, Hendrikus (Jurnal GeoEkonomi, 2025)
The main revenue of Indonesia's finances comes from tax collection, which plays an important role in state revenue. The government relies heavily on taxes as a source of revenue to fund maintenance and development to improve people's welfare. This study aims to evaluate the influence and relationship between the possibility of fraud detection, the tax system, tax ethics, fairness, and discrimination on the perception of tax evasion ethics. The research method used is quantitative with the Purposive Sampling technique for sampling. The data analysis technique used was multiple linear regression analysis, with a total of 100 samples registered at KPP Pratama Samarinda. The results of this study show that the possibility of detecting fraud and the tax system has no effect on the perception of tax evasion ethics, while tax ethics, fairness, and discrimination have a positive influence on the perception of tax evasion ethics.